If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -23 = -4x + 7 Reorder the terms: -23 + x = -4x + 7 Reorder the terms: -23 + x = 7 + -4x Solving -23 + x = 7 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. -23 + x + 4x = 7 + -4x + 4x Combine like terms: x + 4x = 5x -23 + 5x = 7 + -4x + 4x Combine like terms: -4x + 4x = 0 -23 + 5x = 7 + 0 -23 + 5x = 7 Add '23' to each side of the equation. -23 + 23 + 5x = 7 + 23 Combine like terms: -23 + 23 = 0 0 + 5x = 7 + 23 5x = 7 + 23 Combine like terms: 7 + 23 = 30 5x = 30 Divide each side by '5'. x = 6 Simplifying x = 6
| 18x^2+16x=0 | | 4n(x-y)+3n(x+y)-2=equation | | 5m^2+120=55m | | a^2-11a=-28 | | -8x+16=-15x+10 | | .1x=97 | | 3(7x-3)=27 | | .1x+x=97 | | v^2=-24+10v | | 2(g-4)=5g+7 | | .3x+x=208 | | 3(x-5x)+2(xy+8x)+(-8xy)=equation | | 1/2(10x-3)=3 | | 4p^2=-12p+40 | | r=9-3i | | z^2-5z=33+3z | | 458/1000 | | x-.4x=54 | | -7+9=a+5(3) | | 5.1+3w=-1.2 | | 9(2(4)+3)-12(4)= | | 7n^2=42n+112 | | 16x^5y^4-4x^3y^2= | | -9/10+6/5 | | 16x+8=88 | | 9(2(3)+3)-12(3)= | | 5=7h/37 | | n^2=-24-10n | | 5/3j=15 | | 7+I/5=-4 | | 10d-5=4d+7 | | -6+12t-8t=6 |